Phenotypical characterization of lymphocytes infiltrating regressing papillomas. - Knowles, G (1996)
Papillomavirus-induced lesions often regress spontaneously in both humans and animals. Papilloma regression is deemed to be due to a cell-mediated immune response, the nature of which is still ill defined, and is accompanied by immune cell infiltrates. To gain further information on the nature and role of the immune cells present in regressing papillomas, we have analyzed biopsies of papillomas induced in the soft palate of cattle by bovine papillomavirus type 4 (BPV-4) and have phenotypically characterized and quantified the lymphocytes present in these lesions. Eleven papilloma biopsies and seven biopsies of noninfected palate were analyzed for the presence of activated CD4+, CD8+, and gamma delta(WC1+) lymphocytes. We found large numbers of lymphocytes in the subepithelial derma of papillomas but not in normal palate tissue; these cellular masses consisted predominantly of CD4+ lymphocytes, with only a few CD8+ and gamma delta(WC1+) lymphocytes, generally positioned at the periphery of these masses. All three subtypes of lymphocytes were found interdigitated with the cells of the basal layer both in papillomas and in normal palate tissue, but while basal layer CD8+ and gamma delta(WC1+) T cells were detected with similar frequencies in papillomas and uninfected palate, basal layer CD4+ T cells were much more frequent in papillomas. CD4+, CD8+, and gamma delta(WC1+) lymphocytes were found in the suprabasal layers of papillomas, but the CD8+ and gamma delta(WC1+) T cells were more numerous and had migrated further into the differentiating keratinocytes of the papilloma fronds than the CD4+ T cells. We conclude that T-cell infiltration is characteristic of regressing BPV-4 papillomas, that CD4+ lymphocytes are specifically and massively recruited into the regressing papillomas, and that although all three lymphocyte subsets can penetrate the papilloma, only the CD8+ and gamma delta(WC1+) lymphocytes are able to migrate into the fronds. These results suggest that all three lymphocyte subsets have an important role to fulfill during natural regression of papillomas.